METODE ANALYTICAL HIERARCHY PROCESS DAN TAGUCHI LOSS FUNCTION UNTUK PENENTUAN PERINGKAT SUPPLIER - Robertus Bellarminus Krisna Wijaya; Febriana Wurjaningrum (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The aim of this study is to determine priority of several criterias which is considered in arranging supplier ranking and furtherly used as the basis of supplier selection.Method implemented in this study are Analytical Hierarchy Process (AHP) and Taguchi Loss Function. The function of AHP is to determine criterias, whereas Taguchi Loss is used to identify supplier ranking with quality, price, warranties and claim policies, delivery, technical capabilities, and communication system criterias.  The findings show that the main criteria wanted by the company is quality with the highest weight  among other criterias, i.e 0.393. PT Surya Inti Artha emerges as the best supplier because have the smallest Weighted Taguchi loss value